Validation of learning environment inventory for secondary school contexts - Nurulhuda Md Hassan; Norliza Abdul Majid; Nur Khairunnasuha Abu Hassan (Institute of Advanced Engineering and Science, 2020)
This study was conducted to describe the validation of learning environment inventory (LEI) for secondary school contexts. A survey method was used for data collection through the 20-item LEI. This study consists of two phases. In Phase 1, an exploratory factor analysis (EFA) was conducted using the Statistical Package for Social Sciences (SPSS 21) involving data collected from 150 students, which resulted in the extraction of four factors related to learning environment; (a) Learner-centered, (b) Knowledge-centered, (c) Assessment-centered, and (d) Community-centered. A confirmatory factor analysis (CFA) was carried out in Phase 2 with a new sample (N = 268) which resulted in strong model fit estimation. Such results confirmed the factor structure of Phase 1 and resulted in a final 12-item scale, which may be considered as an acceptable model.